2016
DOI: 10.1016/j.msea.2016.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Size effects on flow stress behavior during electrically-assisted micro-tension in a magnesium alloy AZ31

Abstract: As one of the promising micro-manufacturing technologies, micro-forming has economical and ecological advantages in terms of mass and near-net-shape production. However, size effects increasingly affect material performances with scaling down geometry and process parameters and consequently hinder applications of micro-forming. Electrically-assisted (EA) micro-forming may have the potential to minimize the size effects. In order to investigate the size effects in the EA micro-forming, uniaxial tension tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…However, the softening effect is weakened when the current is present. This result indicates that the current can weaken the grain size effect, which corresponds to the result of Wang et al [25]. In order to investigate the grain size effect on the EA tension, the EA tensile tests of various grain sizes and N values were carried out, as shown in Figure 3.…”
Section: Ea Uniaxial Tensile Testsupporting
confidence: 68%
See 1 more Smart Citation
“…However, the softening effect is weakened when the current is present. This result indicates that the current can weaken the grain size effect, which corresponds to the result of Wang et al [25]. In order to investigate the grain size effect on the EA tension, the EA tensile tests of various grain sizes and N values were carried out, as shown in Figure 3.…”
Section: Ea Uniaxial Tensile Testsupporting
confidence: 68%
“…They believed that when the current was applied, the data dispersion would be reduced. Their studies indicated that the current can weaken the size effect [25,26]. Compared with the tensions at room temperature, oven-heated and air-cooled conditions, the fracture stresses were smallest and the fracture strains were largest in the EA tension [27].…”
Section: Introductionmentioning
confidence: 99%
“…The grain boundary thickness (t gb ) was determined using Eq. (7) [38], where k is a material constant and d g is the grain size (9 lm), k was set to a midpoint value equal to 0.125 [17]. Other values of k were created around the midpoint to study the effect of grain boundary thickness, shown in Table 4.…”
Section: Model 2: Grain and Grain Boundary Model (Scaled Model)mentioning
confidence: 99%
“…It has been shown that in steady-state circumstances, the electroplastic effect can be fully modeled and predicted using a conventional energy balance and thermal softening approach that assumes 100% bulk (homogeneous) Joule heating [9,10]. These works use electricity to heat a part but allow the temperature to stabilize before starting deformation.The steady-state modeling approach implemented into a finite element analysis (FEA) cannot predict the transient stress drop caused by pulsed electric current even though the correct temperature profile is predicted [11][12][13].Experimental results comparing the flow stress results of specimen heated in a furnace to the same temperatures seen through electrically assisted deformation found that electrically assisted deformation had a lower stress than thermally assisted, suggesting bulk Joule heating cannot fully explain the transient electroplastic effect [7,[14][15][16][17][18]. Theories have been developed to explain the transient nature of the electroplastic effect; these include (a detailed review of electroplastic theories and models can be found in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation